The Effect Of Financial Literature, Lifestyle, Income, And Gender On The Financial Behavior Of The Millenial Generation - Elitasari, Ardiana; Wiyono, Gendro; Maulida, Alfiatul (Invoice : Jurnal Ilmu Akuntansi, 2022)
This study was conducted to test whether financial literacy, lifestyle, income and gender on the financial behavior of the millennial generation. The selected method used in this study is a quantitative method. This type of research uses descriptive and quantitative statistics, which are used to determine the level of financial literacy and what influences financial behavior in students of the Faculty of Economics, Universitas Sarjanawiyata Tamansiswa. The variables used are financial literacy behavior as the dependent variable, lifestyle, income and gender as independent variables. The sample is part of the selected population obtained based on certain procedures that can represent the population. So based on the calculation of the sample using the Slovin formula, the research sample was obtained as many as 80 active student respondents from the 2017 - 2020 class. The sampling technique was based on research needs. This means that purposive sampling is more used by researchers if a study requires a sampling technique in this study, namely using a purposive sampling technique, The results of the analysis show that financial literacy has no effect on financial behavior, lifestyle has a positive effect on financial behavior, lifestyle has a positive effect on financial behavior and lifestyle has a positive effect on financial behavior.